Making particle boards from plastic waste and wood waste in community groups in village building rejo tanjung morawa district deli serdang district (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Plastic waste and wood waste in Bangun Rejo Village in Tanjung Morawa Sub-District, Deli Serdang Regency, North Sumatra Province, located 35 km east of Medan City Center, is still not managed and utilized as a value-added product. Plastic waste and wood waste can be processed into particle boards for building materials. Collection and sampling of raw materials for polystyrene plastic waste (steroform) and sawdust wood waste have been carried out from Bangun Rejo Village, Tanjung Morawa District, Del Serdang Regency. Furthermore, polystyrene plastic waste and sawdust wood waste were prepared at the USU FMIPA Polymer Chemistry Laboratory in Medan for the manufacture of particle board. Laboratory scale particle board manufacturing is done using xylene solvent and binder using press molding techniques and mold size 15 cm x 10 cm x 0.8 cm with optimum ratio of plastic waste with wood waste (60 g: 60 g). Particle board yields are adjusted to the Indonesian National Standard (2006), which can be used as wall or housing flooring. Solutions offered to community groups in the village in the program. Training activities on the preparation of materials and the manufacture of particle boards from plastic waste and wood waste, as building materials, were carried out on August 20, 2019 at the Bangun Rejo Village Office, Tanjung Morawa District. Furthermore, it is recommended that the community groups in the village be guided to form a particle board manufacturing group under the auspices of the University of North Sumatra.